Propuesta de Implementacion del Marketing Digital como Herramienta de Competitividad y Rentabilidad en el Desarrollo Financiero de la Empresa (2023)
Taking into account the importance that digital technologies have for the company MagicTour Colombia SAS and knowing the dynamics of its business, we set out to carry out this project in order to achieve benefits of competitiveness and financial development, due to the fact that new digital technologies allow having a broader approach, through tools, such as the use of information and communication technologies (ICT). The main directions that will be implemented will carry out each and every one of the processes that will promote the company's products and services, increasing visibility and recognition, boosting sales, locating customers with the highest qualified potential and working on the factors that contribute to continue maintaining a close relationship with old customers, achieving improvements inspired by their opinions and generating great loyalty. The general objective of research through digital marketing is to promote and position itself as an efficient and competent brand. This is how it will be possible to favor and energize the tourism sector, discovering important values such as: consumer awareness and motivation to purchase tourism services. Thus, with the use of these resources, it will achieve financial improvements that will contribute to the company increasing its investments. The efficiency and performance of this proposal will also obey the financial modules, which seek to use internal and external variables to achieve a competitive approach, with financial and technological capabilities. The research is carried out through various studies, articles and bibliographic sources that expose the evolution of tourism. Within this framework, new changes are evident that transform and revolutionize digital tourism marketing and that will be a key element for the adoption and application of MagicTour Colombia in the financial world. In short, the proposal will serve to establish strong communication with the target audience, attract new potential customers and modernize the offer for customers. Thus, defining the financial goals for the growth of the company.